The Outcome of Laparoscopic Ureterolithotomy-the Initial Experience in a Divisional Level Tertiary Hospital (Bangladesh Journal of Urology, 2023)
Objectives : To see the outcome of laparoscopic ureterolithotomy as a beginner Methodology: This was an observational study that was conducted in the Department of Urology, Rangpur medical college from the period from January 2019 to June 2021. The patient’s ages range from 20 years to 60 years. The patients were selected from those with urinary stone disease and were admitted in the urology department. Those with large impacted stones in the ureter with good renal and cardiac functional status were selected. Laparoscopic ureterolithotomy via transperitoneal approach was performed in every case under general anesthesia. DJ stent was given in every case, and the ureterotomy wound was closed with 4-0 round body vicryl. All patients were mobilized and returned to oral feeding on the morning of 1st postoperative day. The catheter was removed on 2nd postoperative day, and the drain was removed on the third postoperative day if the drainage level fell below 50 mL. The D-J catheter was removed under local anesthesia between the second and fourth postoperative weeks. Complications were classified according to the modified Clavien classification system [12]. All patients were given follow-up for 3 months. IVU was done in every case to evaluate stricture at 3rd month of follow-up. The data were recorded and analyzed with Microsoft excel software 2021.Result : Total 25 cases were recorded. The mean patient age was 39.3± 5.9 years. There were 16 male (63.3%) male and 9 (26.7%) female patients in the study. Stones were located on the right side in 17 (62.9%) patients and on the left side in 8 (37.1%) patients. The size of the stones varied from 12 to 19 mm, and the mean stone size was 15 ±2.5 mm. The mean operative time was 125± 8.9 minutes. Intraoperative insertion of the D-J stent was performed in all patients. The D-J catheter was removed under local anesthesia between the second and fourth postoperative weeks. Complications were classified according to the modified Clavien classification system [12].Conclusion : Laparoscopic ureterolithotomy can be considered an intermediate step in gaining experience and developing the necessary skills in utilizing the laparoscopic approach in more complicated reconstructive or radical urological surgery. As a beginner in laparoscopic procedure, the outcome of this laparoscopic ureterolithotomy in our unit is satisfactory, and patient compliance is very good.Bangladesh J. Urol. 2022; 25(1): 37-44